Saltatory rolling circle amplification assay for simple and visual detection of Listeria monocytogenes in milk and milk products. (February 2023) - Prasad, M.C.B.; Milton, A.A.P.; Menon, V.K.; Ghatak, S.; Srinivas, K.; Momin, K.M.; Vineesha, S.L.; Das, S.; Sen, A.; Latha, C.; Sunil, B.; Jolly, D.
Abstract: A novel saltatory rolling circle amplification (SRCA) assay was established for prompt identification of Listeria monocytogenes in milk and Indian milk cake (kalakhand) . The SRCA and conventional PCR were independently able to detect 63 fg and 630 fg L . monocytogenes DNA per reaction, respectively. The detection limit of SRCA was evaluated in artificially contaminated milk and kalakhand. In milk, without any enrichment, SRCA was able to detect 4.4 × 10 2 cfu mL −1 of milk, indicating 100-fold greater sensitivity than PCR (4.4 × 10 4 cfu mL −1 ). After enrichment up to 3 h and 6 h, detection in SRCA improved to 4.4 cfu mL −1 of milk. Spiking studies in kalakhand showed 10-times better results for SRCA than PCR. The study illustrates that the developed SRCA-based test is sensitive, cost-effective, rapid, and most importantly simple for the detection of L. monocytogenes and it can be adopted for on-site detection of L. monocytogenes in a variety of milk and milk products.